2018
DOI: 10.1186/s40621-018-0138-y
|View full text |Cite
|
Sign up to set email alerts
|

You can have your breastmilk and safe sleep too: a preliminary analysis of infant safe sleep data in a Midwestern home visiting program

Abstract: BackgroundSudden unexpected infant death (SUID) accounted for approximately 3700 infant deaths in the US in 2015. SUID risk factors include prone sleeping, bed-sharing, soft bedding use, and maternal smoking. Infant safe sleep data in at-risk communities are difficult to obtain and home visiting programs can add to what we know. This study’s purpose is to determine how often caregivers enrolled in home visiting programs provide safe sleep environments for their infants in relation to breastfeeding status and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In fact, breastfeeding was not correlated with bedsharing in this sample. These results are consistent with another study of breastfeeding and bedsharing among women receiving home visiting services (Hussain et al, 2018). Prior studies in the United Sates that link bedsharing to increased breastfeeding have primarily studied the general population or socioeconomically advantaged samples (Hauck et al, 2008; Huang et al, 2013); our study points to the need for further research with low-income and racially/ethnically diverse groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, breastfeeding was not correlated with bedsharing in this sample. These results are consistent with another study of breastfeeding and bedsharing among women receiving home visiting services (Hussain et al, 2018). Prior studies in the United Sates that link bedsharing to increased breastfeeding have primarily studied the general population or socioeconomically advantaged samples (Hauck et al, 2008; Huang et al, 2013); our study points to the need for further research with low-income and racially/ethnically diverse groups.…”
Section: Discussionsupporting
confidence: 93%
“…The AAP also advises that infants should sleep on a separate surface in the same room as their caregivers for the first 6 months (Moon & Task Force on Sudden Infant Death Syndrome, 2016). While some studies indicate that bedsharing facilitates breastfeeding (McKenna & Gettler, 2016; Mileva-Seitz et al, 2017), parents are discouraged from sleeping with their infants due to the increased risk of sleep-related death (Hussain et al, 2018; Moon & Task Force on Sudden Infant Death Syndrome, 2016). Nevertheless, infant bedsharing remains a common practice in the United States.…”
mentioning
confidence: 99%
“…Some studies also evaluated the proportion of infants who shared a sleeping surface with a mother who smoked, a practice reported to significant increase in the risk of infant death, as demonstrated in a meta-analysis with an odds ratio of 6.27 (95% CI: 3.94-9.99) [158]. A recent US study [87] found that households with tobacco exposure compared to smokefree households were more likely to adopt practices which could place infants at a greater risk of sudden infant death, with supine positioning used less (75% vs. 88%), and bedsharing (62% vs. 44%) and soft bedding more likely (50% vs. 32%). A study investigating bed-sharing practices among postpartum smoking mothers demonstrated 18.8% reported always bed-sharing; 12.6% almost always bed-share and 45.1% reported sometimes bedsharing, with only 23.6% never bed-sharing [99].…”
Section: Infant Smoke Exposurementioning
confidence: 99%
“…Shapiro-Mendoza et al [127] also reported similar findings, with thick blanket use declining from 56.0% to 27.4% and quilt/comforter coverings declining from 39.2% to 7.9% (using three-year moving averages comparing 1993-1995 to 2008-2010). However, in two recent US studies, it was reported by 39% [47] and 36% [87] of caregivers that they used soft bedding in their infant's sleep environment. Bombard and colleagues described that the most frequently reported types of soft bedding were bumper pads (19%), plush or thick blankets (18%), pillows (7%), positioners (6%) and stuffed toys (3%).…”
Section: Items In An Infant's Sleeping Spacementioning
confidence: 99%
“…Direct observation of the sleep environment is considered the gold standard for assessing infants at risk and for promoting compliance with injury-preventing recommendations [15,16]. For example, home-visiting educators are trained to assess infant sleep environments and provide education to increase protective factors such as breastfeeding [17,18]. However, due to families' limited resources, many infant homes do not qualify for home-visiting programs, or parents are reluctant to participate because of the invasive nature of home visits [17,19].…”
Section: Introductionmentioning
confidence: 99%